ANALYSIS OF FOREIGN EXPERIENCE IN ORGANIZING THE ELECTRONIC LEARNING ENVIRONMENT OF THE HIGHER EDUCATION INSTITUTION - Muydinjonov Ziyodjon Rafiqjon Ugli, Muydinjonov Davlatjon Rafiqjon Ugli, Madrakhimova Makhfuza Akhmedovna; Madrakhimov Shukhratjon Shukurovich (Galaxy International Interdisciplinary Research Journal, 2022)
In the article, it is the need of the hour to study the development achievements in the field of the most advanced education in the world experiences, to use the aspects that are suitable for our national characteristics. We will consider the experience of Great Britain, Australia, South Korea and Japan from the countries with high levels of development, with high educational development and quality indicators recognized by experts.